2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591828
|View full text |Cite
|
Sign up to set email alerts
|

Bed-based instrumentation for unobtrusive sleep quality assessment in severely disabled autistic children

Abstract: The relationship between sleep quality and daytime wellness and performance in severely disabled, autistic children is not well understood. While polysomnography and, more recently, actigraphy serve as means to obtain sleep assessment data from neurotypical children and adults, these techniques are not well-suited to severely autistic children. This paper presents recent progress on a bed sensor suite that can unobtrusively track physiological and behavioral parameters used to assess sleep quality. Electromech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…An early description of, and motivation behind, the design of the bed system used in this study can be found in [ 24 ]. The bed system has been used to compare BCG J-peak detection algorithms [ 1 ], and it was used to investigate the relationship between sleep and daytime behavior and cognitive function in severely disabled children with autism who reside at Heartspring [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An early description of, and motivation behind, the design of the bed system used in this study can be found in [ 24 ]. The bed system has been used to compare BCG J-peak detection algorithms [ 1 ], and it was used to investigate the relationship between sleep and daytime behavior and cognitive function in severely disabled children with autism who reside at Heartspring [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our team at Kansas State University has created a bed-based BCG system designed to monitor and quantify the sleep of children who reside at Heartspring, a residential and day school facility in Wichita, KS dedicated to helping children with specialized needs and severe disabilities, including children who are non-verbal and who have disorders across the autism spectrum [ 24 ]. The goal of this paper, as a follow-on to this prior work, is two-fold: (1) to outline the bed system in detail, and (2) to provide a dataset to the research community that includes ballistocardiographic signals monitored by the bed system—signals that are synchronized with more traditional heart-related signals, where these data originate from adult participants with a variety of ages and health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…BCGs were recorded using four Measurement Specialties FX1902 load cells positioned beneath the corner bedposts. The signal conditioning circuitry employed bandpass filters with corner frequencies of 0.05 and 35 Hz-these circuits are further described in [34]. ECGs were simultaneously recorded using a GE Datex-Ohmeda Cardiocap TM /5 patient monitor.…”
Section: A Data Recordingmentioning
confidence: 99%
“…The most popular method for measuring the ballistocardiogram is by using a force plate or weighing scale and having the subject stand as still as they can to reduce motion artifacts. Other popular modalities include seat or chair-based systems [30], bed-based systems [24], [26], [31]- [35], and wearable systems [36], [37]. The bed-based modality makes the most sense for long-term monitoring and sleep quality assessment of severely disabled children.…”
Section: A Bcg Acquisition Systemmentioning
confidence: 99%
“…The virtual instrument does not apply any additional filtering before saving the data to a file on the PC. More details on the bed-system architecture under development at Kansas State University including a preliminary comparison of estimated BCG HBIs compared to the gold standard ECG R-R intervals can be found in [31] and [38]. This work focuses on utilizing the signals measured from the EMFi sensors to estimate the cardiac B-B intervals from a reconstructed BCG signal.…”
Section: A Bcg Acquisition Systemmentioning
confidence: 99%